Training in hypoxia fails to further enhance endurance performance and lactate clearance in well-trained men and impairs glucose metabolism during prolonged exercise - Lecoultre, V.; Boss, A.; Tappy, L.; Borrani, F.; Tran, C.; Schneiter, P.; Schutz, Y. (Experimental Physiology, 2010)
The aim of this study was to investigate the synergistic effects of endurance training and hypoxia on endurance performance in normoxic and hypoxic conditions (?3000 m above sea level) as well as on lactate and glucose metabolism during prolonged exercise. For this purpose, 14 well-trained cyclists performed 12 training sessions in conditions of normobaric hypoxia (HYP group, n = 7) or normoxia (NOR group, n = 7) over 4 weeks. Before and after training, lactate and glucose turnover rates were measured by infusion of exogenous lactate and stable isotope tracers. Endurance performance was assessed during incremental tests performed in normoxia and hypoxia and a 40 km time trial performed in normoxia. After training, performance was similarly and significantly improved in the NOR and HYP groups (training, P < 0.001) in normoxic conditions. No further effect of hypoxic training was found on markers of endurance performance in hypoxia (training × hypoxia interaction, n.s.). In addition, training and hypoxia had no significant effect on lactate turnover rate. In contrast, there was a significant interaction of training and hypoxia (P < 0.05) on glucose metabolism, as follows: plasma insulin and glucose concentrations were significantly increased; glucose metabolic clearance rate was decreased; and the insulin to glucagon ratio was increased after training in the HYP group. In conclusion, our results show that, compared with training in normoxia, training in hypoxia has no further effect on endurance performance in both normoxic and hypoxic conditions or on lactate metabolic clearance rate. Additionally, these findings suggest that training in hypoxia impairs blood glucose regulation in endurance-trained subjects during exercise.